Numerical modeling and investigation of flow of incompressible non-Newtonian fluids through uniform slightly deformable channel (2023)
Numerical investigations of peristaltic flow of three non-Newtonian viscous fluids arising within modelled gut were performed to show their thermal and hydrodynamic behaviour in the gut. A 3-D numerical model of the human intestine was derived using Autodesk Inventor 2017 and simulated using ANSYS FLUENT 16.0. Thyme and produced Ogi, Soymilk and Sobo are considered working fluids. The density and viscosity of the produced fluid were determined experimentally, while the density and viscosity of the digester were obtained from previous work. The results of the experiments carried out showed that the densities of the produced fluid supplements were; 1024 kg/𝑚3 , 920 kg/𝑚3and 800 kg/𝑚3 for Ogi, soybean milk and sobo respectively; their equivalent viscosities were; 1.095 Pa.s, 0.95 Pa.s, and 0.316 Pa.s. From the results, it can be seen that the velocity behaviour of the four fluids is similar, as is the thermal behaviour. The results also showed that at inlet velocity of 0.005 m/s, Ogi had the largest pressure change of 25 Pa and a heat transfer of Nu=9, while sobo had the smallest heat transfer of Nu=9 among the three fluid supplements produced. Nu=5.